Time to #protest: Selective exposure, cascading activation, and framing in social media - Aruguete, Natalia (2018)
In social media, sharing posts exposes a larger number of users to the preferred content of their peers. As users select or discard content, they collectively highlight facets of events or issues as to promote a particular interpretation. This article describes how social media users frame political events by selectively sharing content that is cognitively congruent with their beliefs. We model cognitive dissonance modeling time-to-retweet and exemplify the proposed theory with a study of recent protest events in Argentina.